Stereo reconstruction from microscopic images for computer-assisted ophthalmic surgery - Peter, Rebekka; Moreira, Sofia; Tagliabue, Eleonora; Hillenbrand, Matthias; Nunes, Rita G.; Mathis-Ullrich, Franziska (International Journal of Computer Assisted Radiology and Surgery, 2024)
Purpose : This work presents a novel platform for stereo reconstruction in anterior segment ophthalmic surgery to enable enhanced scene understanding, especially depth perception, for advanced computer-assisted eye surgery by effectively addressing the lack of texture and corneal distortions artifacts in the surgical scene. Methods : The proposed platform for stereo reconstruction uses a two-step approach: generating a sparse 3D point cloud from microscopic images, deriving a dense 3D representation by fitting surfaces onto the point cloud, and considering geometrical priors of the eye anatomy. We incorporate a pre-processing step to rectify distortion artifacts induced by the cornea’s high refractive power, achieved by aligning a 3D phenotypical cornea geometry model to the images and computing a distortion map using ray tracing. Results : The accuracy of 3D reconstruction is evaluated on stereo microscopic images of ex vivo porcine eyes, rigid phantom eyes, and synthetic photo-realistic images. The results demonstrate the potential of the proposed platform to enhance scene understanding via an accurate 3D representation of the eye and enable the estimation of instrument to layer distances in porcine eyes with a mean average error of 190 μm, comparable to the scale of surgeons’ hand tremor. Conclusion : This work marks a significant advancement in stereo reconstruction for ophthalmic surgery by addressing corneal distortions, a previously often overlooked aspect in such surgical scenarios. This could improve surgical outcomes by allowing for intra-operative computer assistance, e.g., in the form of virtual distance sensors.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Computer-assisted ophthalmic surgery; Depth estimation; Distortion correction; Stereo reconstruction